A fast and sensitive method for the continuous in situ determination of dissolved methane and its [delta]13C-isotope ratio in surface waters - Kleint, Jan F.; Schiller, Amanda; Greule, Markus; Keppler, Frank; Isenbeck-Schröter, Margot (Limnology and oceanography. Methods, 2018)
A fast and sensitive method for the continuous determination of methane (CH4) and its stable carbon isotopic values (δ13C-CH4) in surface waters was developed by applying a vacuum to a gas/liquid exchange membrane and measuring the extracted gases by a portable cavity ring-down spectroscopy analyser (M-CRDS). The M-CRDS was calibrated and characterized for CH4 concentration and δ13C-CH4 with synthetic water standards. The detection limit of the M-CRDS for the simultaneous determination of CH4 and δ13C-CH4 is 3.6 nmol L−1 CH4. A measurement precision of CH4 concentrations and δ13C-CH4 in the range of 1.1%, respectively, 1.7‰ (1σ) and accuracy (1.3%, respectively, 0.8‰ [1σ]) was achieved for single measurements and averaging times of 10 min. The response time τ of 57 ± 5 s allow determination of δ13C-CH4 values more than twice as fast than other methods. The demonstrated M-CRDS method was applied and tested for Lake Stechlin (Germany) and compared with the headspace-gas chromatography and fast membrane CH4 concentration methods. Maximum CH4 concentrations (577 nmol L−1) and lightest δ13C-CH4 (−35.2‰) were found around the thermocline in depth profile measurements. The M-CRDS-method was in good agreement with other methods. Temporal variations in CH4 concentration and δ13C-CH4 obtained in 24 h measurements indicate either local methane production/oxidation or physical variations in the thermocline. Therefore, these results illustrate the need of fast and sensitive analyses to achieve a better understanding of different mechanisms and pathways of CH4 formation in aquatic environments.
Im Titel ist "delta" als griechischer Buchstabe dargestellt
im Titel ist die Zahl "13" hochgestellt
Gesehen am 05.09.2019